Evaluasi Proses dan Pengembangan Layanan Publik di UP PMPTSP Semper Timur dan Kalibaru, Jakarta Utara 2021-2022 - Tondang, Andry Purba; Juwono, Vishnu (JOM, 2024)
This study aims to evaluate the internal processes and development of public services in the One-Stop Integrated Service Implementation Unit (UP PMPTSP) of Semper Timur and Kalibaru Villages, North Jakarta, during the 2021-2022 period. The evaluation was conducted to identify strengths and weaknesses in service delivery, as well as to develop strategies for improving the quality of public services. The research method used was descriptive qualitative with data collection techniques through interviews, observation, and document analysis. The results showed an increase in efficiency in the service processes in both villages, with several innovations in service procedures. However, the study also identified constraints, such as the lack of trained human resources and limited information technology infrastructure. These findings indicate that despite efforts to improve, significant challenges in public service delivery remain. Based on these findings, several improvement measures are recommended, including enhancing human resource capacity through structured training programs, strengthening information technology infrastructure, and improving coordination between relevant agencies to optimize the service process. The limitations of this study include limited time and resources for data collection and the scope of the study, which only covers two urban villages in North Jakarta, so the results may not be fully representative of other areas. It is hoped that this research can serve as a basis for developing better policies in public service delivery in the future.